Control of Anthracnose Disease (Colletotrichum gloeosporioides) Using Nano Chitosan Hydrolyzed by Chitinase Derived from Burkholderia cepacia Isolate E76 - Yadi Suryadi; Tri P. Priyatno; I Made Samudra; Dwi N. Susilowati; Tuti S. Sriharyani; Syaefudin Syaefudin (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2017)
Anthracnose (Colletotrichum gloeosporioides) is one of the important diseases of fruit crops that need to be controlled. This study was aimed to obtain the best formula of hydrolyzed nano chitosan and its potensial in controlling anthracnose. The hydrolyzed chitosan was prepared using chitinase enzyme extracted from Burkholderia cepacia isolate E76. Chitosan nanoparticles were synthesized using ionic gelation method by reacting hydrolyzed chitosan (0.2%) with Sodium tripolyphosphate (STPP) (0.1%) as cross-linking agent using 30–60 minutes stirring condition. The bioactivity of the nano chitosan formula was tested to C. gloeosporioides under in vitro and in vivo assays. The specific enzymatic activity of the purified chitinase was higher (0.19 U/mg) than that of crude enzyme (supernatant) with the purity increased by 3.8 times. Of the four formula tested, Formula A (hydrolyzed chitosan to STPP volume ratio of 5 : 1 with 60 minutes stirring condition) was found good in terms of physical characteristic of the particle. The formula nano chitosan particle had the spherical-like shape with an average particle size of 126.2+3.8 nm, polydispersity index (PI) of 0.4+0.02, and zeta potential (ZP) value of 27.8+0.2 mV. Nano chitosan had an inhibitory activity to C. gloeosporioides in vitro up to 85.7%. Moreover, it could inhibit 61.2% of C. gloeosporioides spores germination. It was shown that nano chitosan was also effective to reduce anthracnose disease severity in vivo when applied as a preventive measure on chili and papaya fruits. This study could be used as a reference for further fruit coating application using nano chitosan as a promising postharvest biocontrol agent to C. gloeosporioides.